Exogenous GM1 ganglioside increases accumbal BDNF levels in rats - Valdomero, Analía (2015)
Gangliosides are compounds that are abundant throughout the CNS, participating actively in neuroplasticity. We previously described that exogenous GM1 ganglioside pretreatment enhances the rewarding properties of cocaine, evidenced by a lower number of sessions and/or dosage necessary to induce conditioned place preference (CPP). Since GM1 pretreatment did not modify cocaine's pharmacokinetic parameters, we suspected that the increased rewarding effect found might be mediated by BDNF, a neurotrophic factor closely related to cocaine addiction. This study was performed to investigate the possibility that GM1 may induce changes in BDNF levels in the nucleus accumbens (NAc), a core structure in the brain's reward circuitry, of rats submitted to three conditioning sessions with cocaine (10. mg/kg, i.p.). The results demonstrate that GM1 administration, which showed no rewarding effect by itself in the CPP, induced a significant increase of BDNF protein levels in the NAc, which may account for the increased rewarding effect of cocaine shown in the CPP paradigm.